Total quality management in education - Mukhopadhyay, Marmar (SAGE, 2020)
This is a completely revised new edition of a very successful text first published in 2001. The author combines extensive literature review with his own experience as institution builder, and his experiments on quality management to develop a practical guide for quality improvement for the education-institutional leaders.
Keywords: Total quality management in education.; School management and organization.; Qualité totale en éducation.; Administration scolaire.; School management and organization; Total quality management in education